Transcranial direct current stimulation (tDCS) over the orbitofrontal cortex reduces delay discounting - Moro, Andrea Stefano; Saccenti, Daniele; Vergallito, Alessandra; Scaini, Simona; Malgaroli, Antonio; Ferro, Mattia; Lamanna, Jacopo (Frontiers in Behavioral Neuroscience, 2023)
Delay discounting (DD) is a quantifiable psychological phenomenon that regulates decision-making.Nevertheless, the neural substrates of DD and its relationship with other cognitive domains are not well understood. The orbitofrontal cortex (OFC) is a potential candidate for supporting the expression of DD, but due to its wide involvement in several psychological functions and neural networks, its central role remains elusive. In this study, healthy subjects underwent transcranial direct current stimulation (tDCS) while performing an intertemporal choice task for the quantification of DD and a working memory task. To selectively engage the OFC, two electrode configurations have been tested, namely anodal Fp1 -cathodal Fp2 and cathodal Fp1 -anodal Fp2. Our results show that stimulation of the OFC reduces DD, independently from electrode configuration. In addition, no relationship was found between DD measures and either working memory performance or baseline impulsivity assessed through established tests. Our work will direct future investigations aimed at unveiling the specific neural mechanisms underlying the involvement of the OFC in DD, and at testing the efficacy of OFC tDCS in reducing DD in psychological conditions where this phenomenon has been strongly implicated, such as addiction and eating disorders.